2022
DOI: 10.1186/s12882-022-02986-2
|View full text |Cite|
|
Sign up to set email alerts
|

Renal thrombotic microangiopathy and nephrotic proteinuria induced by intravitreal injection of aflibercept for diabetic macular edema

Abstract: Background Vascular endothelial growth factor inhibitors (VEGFIs) are used to treat malignant neoplasms and ocular diseases by inhibiting angiogenesis. Systemic use of VEGFIs has various side effects, including hypertension, proteinuria, and thrombotic microangiopathy, but adverse events due to intravitreal injection of VEGFIs have not been fully clarified. Although age-related macular degeneration was initially the most common target of intravitreal injection of VEGFIs, it has also been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…8 Molecular weight distributions can also be used to monitor the progression of kidney disease and to assess the response to treatment. 4,5 The zebrafish pronephros, with its simple and functional segmentation, is a favorable model to study mammalian nephrons, as they share several similarities. 9,10,11,12 Based on the mapping of expressed genes, it has been observed that the pronephric duct, previously thought to be a uniform duct, is actually composed of multiple segments, including the proximal convoluted tubule, proximal straight tubule, distal early tubule, corpuscle of Stannius, and distal late tubule.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Molecular weight distributions can also be used to monitor the progression of kidney disease and to assess the response to treatment. 4,5 The zebrafish pronephros, with its simple and functional segmentation, is a favorable model to study mammalian nephrons, as they share several similarities. 9,10,11,12 Based on the mapping of expressed genes, it has been observed that the pronephric duct, previously thought to be a uniform duct, is actually composed of multiple segments, including the proximal convoluted tubule, proximal straight tubule, distal early tubule, corpuscle of Stannius, and distal late tubule.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Molecular weight distributions of urinary proteins aid in diagnosing different types of kidney disease, including diabetic nephropathy, chronic kidney disease, and glomerulonephritis . Molecular weight distributions can also be used to monitor the progression of kidney disease and to assess the response to treatment. , …”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors have replaced the Supplementary Information (Additional file 1 ).…”
mentioning
confidence: 99%